Implications arising from models of solar irradiance: A reply to Summerhayes' comment on 'The Medieval Quiet Period'. (February 2017) - Bradley, Raymond S; Wanner, Heinz; Diaz, Henry F
Models of solar irradiance have been revised recently, leading to the current view that previous estimates of maximum total solar irradiance (TSI) in the 18th and 19th centuries were too low and should be adjusted upwards to be comparable with values in the 20th century. This adjustment is small (~0.03%) but implies a greater amplitude of irradiance change over recent centuries. This has no bearing on our concept of a Medieval Quiet Period.